Prevalence of Dental Caries in 5-Year-Old Children in a Northeast Brazilian Capital - Katia de Gois Holanda Saldanha; Janaina Rocha de Sousa Almeida; Maria Eneide Leitão de Almeida; Iana Aragão Magalhães; Paulo Goberlânio de Barros Silva (Association of Support to Oral Health Research (APESB), 2023)
Objective: To evaluate the prevalence of dental caries in children aged five years in a Northeast Brazilian Capital (Fortaleza, CE) and its association with sociodemographic conditions, presence of malocclusion, and gingival bleeding. Material and Methods: This is a quantitative, descriptive, observational, and cross-sectional study carried out in a representative sample of 3,582 children aged five years in the city of Fortaleza-CE. Data was collected in public and private schools distributed in the city's Regional Health Coordination (CORES). Each of the six CORES worked with five field teams, participating in inter-examiner training and calibration with a final KAPPA coefficient of 0.87. Data were collected using a clinical form adapted from the SB Brasil 2010 questionnaire on sociodemographic conditions. The indices of dmft, need for treatment, malocclusion, and gingival bleeding were used for oral health conditions. The data were submitted to Pearson's Chi-square or Fisher's Exact tests, and the variables that show values of p<0.05 were submitted to a multinomial logistic regression model (forward stepwise model). Results: 57.1% of children were caries-free, and the mean dmft-d was 1.65 (1.65±2.65). CORES I and VI were the ones that presented the most significant association with caries attacks in all primary molars. The highest percentage of caries in the 2nd upper molar (60.6%), 1st lower molar (59%), and 2nd lower molar (58.8%) were found in children with normal occlusion. There was a significant association between gingival bleeding and caries in all molars and the need for treatment. Conclusion: These results allow us to observe that the prevalence of dental caries in 5-year-old children in Fortaleza is low, although with a tendency to increase.